An examination of the bidirectional relationship between functioning and symptom levels in patients with anxiety disorders in the CALM study. Issue 3 (2nd October 2014) - Brown, L. A.; Krull, J. L.; Roy-Byrne, P.; Sherbourne, C. D.; Stein, M. B.; Sullivan, G.; Rose, R. D.; Bystritsky, A.; Craske, M. G.
Abstract : Background: Patients with anxiety disorders suffer marked functional impairment in their activities of daily living. Many studies have documented that improvements in anxiety symptom severity predict functioning improvements. However, no studies have investigated how improvements in functioning simultaneously predict symptom reduction. We hypothesized that symptom levels at a given time point will predict functioning at the subsequent time point, and simultaneously that functioning at a given time point will predict symptom levels at a subsequent time point. Method: Patients were recruited from primary-care centers for the Coordinated Anxiety Learning and Management (CALM) study and were randomized to receive either computer-assisted cognitive-behavioral therapy and/or medication management (ITV) or usual care (UC). A cross-lagged panel design examined the relationship between functional impairment and anxiety and depression symptom severity at baseline, 6-, 12-, and 18-month follow-up assessments. Results: Prospective prediction of functioning from symptoms and symptoms from functioning were both important in modeling these associations. Anxiety and depression predicted functioning as strongly as functioning predicted anxiety and depression. There were some differences in these associations between UC and ITV. Where differences emerged, the UC group was best modeled with prospective paths predicting functioning from symptoms, whereas symptoms and functioning were both important predictors in the ITV group. Conclusions: Treatment outcome is best captured by measures of functional impairment as well as symptom severity. Implications for treatment are discussed, as well as future directions of research.